Sex-specific longitudinal associations of screen viewing time in children at 2–3 years with adiposity at 3–5 years - Padmapriya, Natarajan (2021)
Objective: Screen-viewing in late childhood has been associated with adiposity and blood pressure (BP), but evidence is lacking at younger ages. To investigate the prospective associations of total and device-specific screen-viewing at age 2–3 years with BMI, sum of skinfold thicknesses and BP among Singaporean children at age 3–5 years. Methods: As part of the Growing Up in Singapore Towards healthy Outcomes (GUSTO) cohort, mothers/caregivers reported the time per day their 2 and 3-year-old children watched/used television, handheld devices and computers. Average screen-viewing time (total, television and handheld-devices) at ages 2 and 3 years was used in the analyses. Height; weight; triceps, biceps and subscapular skinfold thicknesses; and systolic and diastolic BP were measured at ages 3, 4 and 5. Associations of screen-viewing with BMI, sum of skinfold thicknesses and BP in 956 children were investigated using repeated-measures linear regression models. Analyses were further stratified by sex as we found significant interaction. Results: Among boys and girls combined, screen-viewing was positively associated with sum of skinfold thicknesses, but not with BMI or BP. Sex-specific analyses showed significant associations with both BMI and sum of skinfold thicknesses in boys, but not in girls. Screen-viewing was not associated with BP in boys or girls. The increases in mean (95% CI) BMI per hour increase in daily total, television and handheld-devices screen-viewing among boys were 0.12 (0.03, 0.21), 0.18 (0.06, 0.30) and 0.11 (−0.07, 0.29) kg/m2, respectively. The corresponding increases in mean sum of skinfold thicknesses were 0.68 (0.29, 1.07), 0.79 (0.26, 1.32) and 1.18 (0.38, 1.99) mm. Conclusions: Greater screen-viewing at age 2–3 years was associated with later adiposity at 3–5 years in boys, but not in girls. In light of the increasing use of screen devices and cardiometabolic risk in young children, these findings may have important public health implications.